1979
DOI: 10.1021/bi00572a018
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium magnetic resonance study of cholesteryl esters in membranes

Abstract: The ternary systems EYL:H2O (50:50 wt %) containing 1 and 5 mol % cholesteryl palmitate-d31 or 1 and 5 mol % cholesteryl palmitate-16,16,16,16-d3 have been studied. Cholesteryl palmitate-d31 gave a unique deuterium magnetic resonance spectrum corresponding to a homogeneous (delta vQ = 3 and 12 kHz) and a solid phase (deltaVQ = 38 and 118 kHz). From the characteristic spectra and spin-lattice relaxation times, a procedure for calculating the amount of each phase present in the ternary mixture is given resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
(25 reference statements)
2
21
1
Order By: Relevance
“…The C16 fatty acid chain folds back into the bilayer hydrophobic interior [22] with the ester adopting a "horseshoe" conformation. The ester linkage is located near the bilayer interface.…”
Section: Effect Of Mammalian Sterols On Model Membranesmentioning
confidence: 99%
“…The C16 fatty acid chain folds back into the bilayer hydrophobic interior [22] with the ester adopting a "horseshoe" conformation. The ester linkage is located near the bilayer interface.…”
Section: Effect Of Mammalian Sterols On Model Membranesmentioning
confidence: 99%
“…multilamellar liposomes prepared from the same phospholipid (28) and the same situation has also been encountered for the egg phosphatidylcholineICP system (5,6). The apparent increase in ester solubility upon going from liposomes to small vesicles may simply reflect sonication forcing an excess amount of cholesteryl ester into the bilayer, so that the final sample represents a supersaturated system.…”
Section: Discussionmentioning
confidence: 79%
“…In our initial study (1) we by sonication of aqueous dispersions to form highly utilized 31P nmr spectroscopy and found that curved unilamellar vesicles, ester intercalation incholesteryl palmitate (CP) increased the permea-creases substantially, reaching as high as 5 mol% bility of model membranes to ions, whereas (6) while the ester chains appear more disordered cholesteryl linoleate did not. The behavior of the compared to CP in multilamellar liposomes (5). saturated ester CP in egg phosphatidylcholine…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations